(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
White Collar Crime is a socio- economic offence which is generally committed by people of high status or elite class of people in the society. It is done with an intention to receive financial gains by means of committing wrongful activities. Hence, it is a socio- economic offence, it disturbs the economy of a nation where it is committed. It has the impact on the stock markets, international trade, foreign exchange, demand and supply or goods and services etc. In India, there are various laws which has an intention to prevent the occurrence of white collar crimes and tries to punishes the offenders either with imprisonment or fines or both as prescribed in the provisions of Act. Although India as various Act and legal provisions under IPC which deals white collar crimes and its punishment but then also India has witnessed some high profile white collar crimes (in form of scams or scandals) which shocked the nation and disturbs the roots of Indian Economy. Thus, the article tries to give a bird eye view on the criminology of white collar crimes in India. The article also tries to an give an light on various scams and scandals which took place in India. The article also focuses on various act and its legislative intent to prevent white collar crime in India.